Strategy and defence planning meeting the challenge of uncertainty - Gray, Colin S. (Oxford University Press, 2014)
This title explores and examines why and how security communities prepare purposefully for their future defence. Professor Gray argues that our understanding of human nature, of politics, and of strategic history, does allow us to make prudent choices in defence planning.